Forest tenure and the Sustainable Development Goals – A critical view - Katila, P.; McDermott, C.; Larson, A.M.; Aggarwal, S.; Giessen, L. (Elsevier, 2020)
Agenda 2030 and its 17 Sustainable Development Goals (SDGs) form an overarching framework to guide development at all scales from local to global. They are intended to holistically address sustainability across its economic, ecological and social dimensions. A core tenant of this holistic approach is that all dimensions of sustainability are interlinked, such that changes in one dimension can have pivotal effects on others. This paper focuses on land and forest resource tenure as one such pivotal issue that importantly shapes the achievement of the SDGs. It considers the current status of forest tenure globally and analyses critically how the different aspects of tenure rights are included and addressed in the SDG targets and indicators. The main conclusions of this analysis are that land and resource tenure, including forest tenure, is explicitly addressed in specific SDGs, but the way these SDGs, targets and corresponding indicators are formulated leads to only partial inclusion of important aspects of tenure rights.